Nature, art and love in three long poems by Javier Sologuren: Estancias (1960), Recinto (Enclosure, 1967) and La hora (The hour, 1980 - Romero Suárez, Daniel A. (2016)
This paper will analyze three long poems written by Javier Sologuren: Estancias (1960), Recinto (Enclosure, 1967) and La hora (The hour, 1980). These compositions center on the origin and the possibilities of the art, interwoven with a reflection on the nature and love. However, these elements will not be treated with equal intensity in the three aforementioned poems. In Estancias, the reflection on art will be from a very romantic nature perspective, although it will be an archetypal love which will allow greater significance. Then, in Recinto, it will use images of land excavations to show how can it revitalize the past and overcome paralysis of death through poetry. Finally, in La hora, the scenario will be the modern city, as for its vices as for its virtues, where the art and the love are wielded as contrary means to the «spectacle of death».